(untitled) (Analysis in Theory and Applications, 2022)
In this paper, we study the long time well-posedness of 2-D MHD boundary layer equation. It was proved that if the initial data satisfies \|(u_0,h_0-1)\|_H_μ^3,0H_μ^1,2 ε, then the life span of the solution is at least of order ε^2-η for η>0.